Executive Functioning, Muscle Power and Reactive Balance Are Major Contributors to Gait Adaptability in People With Parkinson’s Disease - Caetano, Maria Joana D.; Lord, Stephen R.; Allen, Natalie E.; Song, Jooeun; Paul, Serene S.; Canning, Colleen G.; Menant, Jasmine C. C. (Frontiers in Aging Neuroscience, 2019)
Background and Aim: The ability to adapt gait when negotiating unexpected hazards is crucial to maintain stability and avoid falling. This study investigated cognitive, physical and psychological factors associated with gait adaptability required for obstacle and stepping target negotiation in people with Parkinson’s disease (PD). Methods: Fifty-four people with PD were instructed to either: (a) avoid an obstacle at usual step distance; or (b) step onto a target at either a short or long step distance projected on a walkway two heel strikes ahead and then continue walking. Participants also completed clinical [Hoehn & Yahr rating scale; Movement Disorders Society version of the Unified Parkinson’s Disease Rating Scale motor section (MDS-UPDRS-III)], cognitive [simple reaction time, Trail Making and Stroop stepping (difference between incongruent and standard Choice Stepping Reaction Time, CSRT) tests], physical [hip abductor muscle power and reactive balance (pull test from the MDS-UPDRS-III)] and psychological (Fall Efficacy Scale–International) assessments. Results: Discriminant function analysis revealed Stroop stepping test (inhibitory control) performance was the best predictor of stepping errors across the Gait Adaptability Test (GAT) conditions. Poorer executive function [Trail Making Test (TMT)] and reactive balance predicted poorer stepping accuracy in the short target condition; poorer reactive balance predicted increased number of steps taken to approach the obstacle and the long target; and poorer executive function predicted obstacle avoidance. Weaker hip abductor muscle power, poorer reactive balance, slower reaction time, poorer executive function and higher concern about falling were significant predictors of shorter step length while negotiating the obstacle/targets. Conclusion: Superior executive function, effective reactive balance and good muscle power were associated with successful gait adaptability. Executive function and reactive balance appear particularly important for precise foot placements; and cognitive capacity for step length adjustments for avoiding obstacles. These findings suggest that impaired inhibitory control contributes to stepping errors and may increase fall risk in people with PD. These findings help elucidate mechanisms for why people with PD fall and may facilitate fall risk assessments and fall prevention strategies for this group.